2020
DOI: 10.1101/2020.06.14.150755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indirect and Direct Cannabinoid Agonists Differentially Affect Mesolimbic Dopamine Release and Related Behaviors

Abstract: Abbreviations: 2-AG, 2-arachidonoylglycerol; AA-5-HT, N-arachidonoyl serotonin; ACEA, arachidinoyl-2'chloroethylamide; AEA, arachidonoylethanolamide; B6, C57BL/6J mice; CB1R, cannabinoid type 1 receptor; CB2R, cannabinoid type 2 receptor; CPA, conditioned place aversion; CPP, conditioned place preference; DAR, dopamine autoreceptor; DAT, dopamine transporter; D2R, dopamine receptor D2; D3R, dopamine receptor D3; eCB, endocannabinoid; EPM, elevated plus maze; FAB5, fatty acid binding protein-5; FAB7, fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…3 shows an outline of the methodology employed for the evaluation. The Peng-Robinson [25] equation of state (EoS) was specified for thermodynamic property estimation of streams containing air or light hydrocarbons, while ASME steam tables were selected for the power cycle. All configurations employ the same purification unit and MeOH synthesis loop, with a boiling water reactor (BWR) modelled using kinetics for CO 2 hydrogenation and reverse WGS reactions from Bussche et al [26] operated at 230 • C and 75 bar, within the typical range found in industrial applications [6].…”
Section: Methodsmentioning
confidence: 99%
“…3 shows an outline of the methodology employed for the evaluation. The Peng-Robinson [25] equation of state (EoS) was specified for thermodynamic property estimation of streams containing air or light hydrocarbons, while ASME steam tables were selected for the power cycle. All configurations employ the same purification unit and MeOH synthesis loop, with a boiling water reactor (BWR) modelled using kinetics for CO 2 hydrogenation and reverse WGS reactions from Bussche et al [26] operated at 230 • C and 75 bar, within the typical range found in industrial applications [6].…”
Section: Methodsmentioning
confidence: 99%